2003
DOI: 10.1007/s00284-002-3966-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Phytase from Pseudomonas syringae MOK1

Abstract: A phytase (EC 3.1.3.8) from Pseudomonas syringae MOK1 was purified to apparent homogeneity in two steps employing cation and an anion exchange chromatography. The molecular weight of the purified enzyme was estimated to be 45 kDa by sodium dodecyl sulfate-polyacrylamide gel electrophoresis analysis. The optimal activity occurred at pH 5.5 and 40 degrees C. The Michaelis constant (Km) and maximum reaction rate (Vmax) for sodium phytate were 0.38 mM and 769 U/mg of protein, respectively. The enzyme was strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 17 publications
1
12
1
Order By: Relevance
“…phytase activity of samples collected from each purification step was measured on phytic acid as described by Heinonen and Lahti et al with minor modifications (Cho et al, 2003;Heinonen and Lahti, 1981;Sanikommu et al, 2013;Yoon et al, 1996). A unit (U) of phytase activity was defined as the amount of enzyme required to release 1 µmol of inorganic phosphate per min under the assay conditions.…”
Section: Figmentioning
confidence: 99%
“…phytase activity of samples collected from each purification step was measured on phytic acid as described by Heinonen and Lahti et al with minor modifications (Cho et al, 2003;Heinonen and Lahti, 1981;Sanikommu et al, 2013;Yoon et al, 1996). A unit (U) of phytase activity was defined as the amount of enzyme required to release 1 µmol of inorganic phosphate per min under the assay conditions.…”
Section: Figmentioning
confidence: 99%
“…Phytase activity was measured in an assay mixture containing 100 l of sodium phytate (0.5 w/v) prepared in 0.2 M sodium acetate buVer pH 5.5 [1,5,7,8] and 100 l of suitably diluted enzyme. The reaction was stopped by adding an equal volume (200 l) of 15% trichloroacetic acid after 30 min of incubation at 50°C [3].…”
Section: Enzyme Assaymentioning
confidence: 99%
“…The activity of this enzyme was inhibited by thiolacting agents, such as Zn 2+ , Cu 2+ , Hg 2+ , and iodoacetic acid, and activated weakly by the disulfide bridge-reducing agents, DTT and 2-mercaptoethanol (Table 3), clearly indicating the requirement of free thiol group(s) of Cys residue(s) for the activity. The activity of some other HAP phytases of bacterial origin were also inhibited by Cu 2+ and Zn 2+ , though the level of inhibition was different (Cho et al, 2003;Fu et al, 2008;Huang et al, 2006). The alignment showed that the mature portion of this enzyme contains eight Cys residues, of which five are conserved in bacterial HAP phytases examined and the remaining three are conserved in six phytases, including H. alvei phytase.…”
Section: Discussionmentioning
confidence: 97%